(untitled) (Research Announcements "Heritage BG", 2025)
By 1914, the first stage of the organizational development of Bulgarian technical specialists was completed and the national engineering and architectural association was established. After World War I, socio-economic conditions changed and the technical community faced serious challenges. In search of solutions to these problems, attempts were made to reorganize the existing Association, and other professional associations were created. This article shows the evolution in the attitudes and activities of this professional group during a very dynamic historical period from 1919 to 1939.